Construct Validation of Self-Determination Theory in Second Language Scale: The Bifactor Exploratory Structural Equation Modeling Approach - Alamer, Abdullah (Frontiers in Psychology, 2021)
The present study aimed to assess the construct validity of the Self-Determination Theory in Second Language Scale (SDT-L2; Alamer, 2021). The study involved 266 undergraduate students learning English as a second language (L2) in Saudi Arabia. The factorial structure of the SDT-L2 was examined using the advanced bifactor-Exploratory Structural Equation Modelling (ESEM) method. The scale provided adequate composite reliability and the bifactor-ESEM provided unique details about the multidimensionality of the scale which accounted for the specific constructs (i.e., intrinsic, identified, introjected, and external regulations) and the general constructs (i.e., autonomous motivation and controlled motivation), and allowed for assessment of convergent and discriminant validity. Predictive validity was established by showing that autonomous motivation significantly predicted L2 performance, while controlled motivation did not. Overall, the study demonstrated the usefulness of the bifactor-ESEM for construct validation purposes and the results showed that SDT-L2 is a valid scale to assess students’ L2 motivation based on SDT perspective